Analisis Faktor Yang Memengaruhi Niat Beli Produk Skincare Halal - Faisal Harits Al Habib; Anas Hidayat (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to explain what factors encourage Muslim consumers to intend to purchase halal skincare products. The sample used in this research was 210 respondents who were active students in Yogyakarta. The sampling technique uses Purposive Sampling technique. The analysis technique used is SEM (Strucrural Equation Modeling) analysis which was processed with the help of the AMOS 24 application. The variables used in this research consist of 4 variables including intrinsic religiosity, knowledge of halal products, awareness of halal products, and intention to purchase halal skincare products. . The results of this research show that there is a positive and significant influence between intrinsic religiosity, halal product knowledge, halal product awareness, and intention to purchase halal skincare products.